Review on the application of Traditional Chinese Medicine nursing techniques in the prevention of thrombus in arteriovenous fistula (中医护理技术在动静脉内瘘血栓防护中应用的研究进展) - LI Xiuli (李秀丽); DENG Jianhua (邓建华); E Haiyan (鄂海燕); TANG Ling (唐玲) (中西医结合护理)
Thrombosis is a common complication of arteriovenous fistula. This article reviewed the risk factors of the generation of thrombosis in arteriovenous fistula, and conventional nursing measures of prevention. Specifically, the mechanism and application of TCM nursing technology in preventing thrombosis was included in the current study, in order to provide guidance for clinical nursing practices. (血栓形成是动静脉瘘患者常见并发症。本文从动静脉内瘘血栓形成的相关因素、预防血栓的常规护理措施、中医护理技术在预防血栓中的应用以及中医护理技术在防治血栓的作用机理四个方面进行综述, 以期为临床护理提供参考和指导。)